Research on Video Sample Collection and Processing Methods Based on Artificial Intelligence Platform - Hu, An; Wang, Qi; Xu, Xiaoguang; Zhao, Yao; Ji, Qian; Pei, Lei (Procedia computer science, 2024)
This paper summarizes the video sample collection and processing methods based on artificial intelligence platform, focusing on video noise cancellation, content segmentation and classification, and feature extraction and representation techniques. The paper believes that the deep learning technology, especially the convolutional neural network, shows great potential in image recognition and video analysis, and effectively improves the level of automation and accuracy of video processing. This paper discusses the importance of building a large-scale and high-quality video sample library, and how to improve the processing efficiency and accuracy of video data through intelligent technology.